(untitled) (REMUNOM, 2025)
The rise in the use of anabolic androgenic steroids among athletes and non-athletes, driven by aesthetic standards, has transformed the issue into a public health problem. This study investigated the severe impacts of the indiscriminate use of these substances, addressing their adverse effects, ranging from cardiovascular, hepatic, and endocrine complications to neurological and behavioral changes such as depression and aggression. The methodology consisted of analyzing scientific articles from databases such as PubMed and SciELO, published between 2015 and 2025, focusing on evidence on the risks of AAS and the role of pharmacists. The research results confirm that the use of AAS, often in doses higher than therapeutic, leads to serious consequences, such as hypogonadism, kidney failure, liver damage, and muscle dysmorphia. The study highlights pharmacists as essential healthcare professionals in combating this problem. Their role goes beyond controlled dispensing, encompassing pharmaceutical care, awareness, and education of the population about the risks. Pharmacists can work in pharmacies, gyms, and schools, providing guidance on the dangers and promoting the rational use of medications, proving to be a key player in preventing the abuse of AAS.